Sleep Quality and the Subjective Experience of Autobiographical Memory: Differential Associations by Memory Valence and Temporality. Issue 6 (31st August 2017) - Lukowski, Angela F.; Valentovich, Valentina; Bohanek, Jennifer G.; Slonecker, Emily M.
Summary: The primary goal of the present research was to examine associations between sleep quality and the subjective experience of autobiographical events. In an online study, 141 university students reported on past events that varied by valence (positive or negative) and temporality (most significant or from the previous 2 weeks); they also completed measures of sleep quality and depression. Relative to participants with good sleep quality, participants with poor sleep quality thought more about their negative experiences, reported negative events that occurred more frequently, and used more negative emotion words when describing recent negative events. In some instances, depressive symptoms mediated the relation between sleep quality and elements of autobiographical reports. Future experimental work should examine the directionality of these effects, with the ultimate goal of improving sleep quality, mental health, and the manner in which individuals discuss and make meaning of their negative life events. Copyright © 2017 John Wiley & Sons, Ltd.